2015
DOI: 10.1080/02699931.2015.1116978
|View full text |Cite
|
Sign up to set email alerts
|

Learning to fear a second-order stimulus following vicarious learning

Abstract: Vicarious fear learning refers to the acquisition of fear via observation of the fearful responses of others. The present study aims to extend current knowledge by exploring whether second-order vicarious fear learning can be demonstrated in children. That is, whether vicariously learnt fear responses for one stimulus can be elicited in a second stimulus associated with that initial stimulus. Results demonstrated that children's (5-11 years) fear responses for marsupials and caterpillars increased when they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…In most experimental observational SFL protocols in non-human animals, all modalities are used in conjunction as the demonstrator is directly exposed to the observer [28, 29]. Some studies use a second-order observational SFL procedure [30], which is analogous to second-order classical FC [31]. Second-order SFL begins with standard observational fear learning procedure in which a neutral CS is paired with the demonstrator’s expression of fear, and then in the subsequent training session, this CS (now called the first-order CS or CS1) is paired with a novel cue (second-order CS or CS2) [30].…”
Section: How Is Social Fear Learning Studied?mentioning
confidence: 99%
See 1 more Smart Citation
“…In most experimental observational SFL protocols in non-human animals, all modalities are used in conjunction as the demonstrator is directly exposed to the observer [28, 29]. Some studies use a second-order observational SFL procedure [30], which is analogous to second-order classical FC [31]. Second-order SFL begins with standard observational fear learning procedure in which a neutral CS is paired with the demonstrator’s expression of fear, and then in the subsequent training session, this CS (now called the first-order CS or CS1) is paired with a novel cue (second-order CS or CS2) [30].…”
Section: How Is Social Fear Learning Studied?mentioning
confidence: 99%
“…Some studies use a second-order observational SFL procedure [30], which is analogous to second-order classical FC [31]. Second-order SFL begins with standard observational fear learning procedure in which a neutral CS is paired with the demonstrator’s expression of fear, and then in the subsequent training session, this CS (now called the first-order CS or CS1) is paired with a novel cue (second-order CS or CS2) [30]. The most commonly used measures of learning acquired through observational SFL are changes in autonomic activity, such as skin conductance responses, SCR, which are tested mostly in human studies [23, 25, 32]; behavioral threat responses, such as immobility or freezing, which are used in animal research [26, 33]; and avoidance behavior tested both in humans and animals [27, 3437].…”
Section: How Is Social Fear Learning Studied?mentioning
confidence: 99%
“…Acquisition. (Dunne et al, 2017;Reynolds et al, 2017). The significant pairing type  time interaction showed that avoidance preferences changed over time depending on the type of face children saw animals with, F(2, 116) = 7.40, p = .001, η 2 p = .11 (95% CIs [0.021, 0.22]).…”
Section: Avoidance Preferencesmentioning
confidence: 96%
“…The concept of vicarious learning has been applied in many different fields, including organizational learning [9,58], entrepreneurship [59,60], social commerce [61], individual learning [10], fear-learning [62], education [63], and training [64]. Vicarious learning may be viewed as a component of social learning theory, originally derived from the work of psychologist Albert Bandura [65,66].…”
Section: Review Of Vicarious Learningmentioning
confidence: 99%